The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1258/phleb.2012.012s35
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic tests and strategies in venous thromboembolism

Abstract: Venous thromboembolism (VTE) is a term including deep vein thrombosis (DVT) and pulmonary embolism (PE). Timely and accurate diagnosis of both is essential as delayed or missed diagnoses can result in death or longer term complications. Patients with suspected DVT should initially undergo a pretest probability Wells score. Depending on pretest probability Wells score they should then either proceed to two-point ultrasound scanning or D-dimer testing. Likewise, patients suspected of PE should undergo a two-leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 70 publications
(60 reference statements)
1
16
0
1
Order By: Relevance
“…The lowest levels of agreement were found for items related to physical examination for local symptoms in the affected limb (e.g., presence of swelling, changes in skin temperature, skin discoloration) and worsening limb pain. The low levels of agreement for these local signs and symptoms confirm previous work that has found that clinical assessment for possible DVT (particularly in the early stages) is highly subjective and even well‐trained clinicians may miss early clinical signs (Falck‐Ytter et al., ; Songwathana et al., ; Strijkers et al., ; Tan et al., ; Tenna et al., ).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The lowest levels of agreement were found for items related to physical examination for local symptoms in the affected limb (e.g., presence of swelling, changes in skin temperature, skin discoloration) and worsening limb pain. The low levels of agreement for these local signs and symptoms confirm previous work that has found that clinical assessment for possible DVT (particularly in the early stages) is highly subjective and even well‐trained clinicians may miss early clinical signs (Falck‐Ytter et al., ; Songwathana et al., ; Strijkers et al., ; Tan et al., ; Tenna et al., ).…”
Section: Discussionsupporting
confidence: 75%
“…Homan's sign (pain in the calf when there is dorsiflexion of the foot) is no longer routinely used as a diagnostic tool for DVT due to its lack of sensitivity and specificity (Bacon, ). The reasons for the poor prognostic value of clinical signs are that each patient may present differently depending on site and size of thrombus and that the clotting process can also mimic many other disease states (Hotoleanu, Fodor, & Suciu, ; Strijkers, Cate‐Hoek, Bukkems, & Wittens, ; Tan, Van Rooden, Westerbeek, & Huisman, ; Tenna, Kappadath, & Stansby, ). Assessing postoperative orthopaedic patients also poses its own unique challenges, particularly as the surgical procedure also contributes to swelling and oedema in the affected limb (Schiff et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis of DVT is usually based on a careful clinical evaluation, D-dimer levels and visualization of the thrombosis (Goodacre et al 2006 ; Tenna et al 2012 ). In our present study all patients were initially evaluated with clinical examination, D-dimer and ultrasound examination; venography was performed only if DVT was still suspected but not visualized after this initial examination.…”
Section: Discussionmentioning
confidence: 99%
“…To date, lower limb phlebography has been considered to be the gold standard for the diagnosis of DVT; however, as it is an invasive and high-cost procedure, the application of lower limb phlebography in the diagnosis of liver DVT is limited (10). Color and spectral Doppler ultrasonography is commonly used in the diagnosis of DVT in lower limb veins; however, ultrasonography requires that patients move continually, which can increase patient suffering and is a time-consuming process.…”
Section: Introductionmentioning
confidence: 99%